Bibliometric analysis on cultural tourism and depopulation in rural areas - Simón-Isidoro, Selene; Álvarez-Herranz, Agustín (Revista de Ciencias Sociales, 2023)
Today, tourism has had to readapt itself to the global circumstances brought about by the Covid-19 pandemic. As a result, it has had to reorient itself and find new lines of investigation. Cultural tourism, a by-product of this situation, has found the rural environment to be the ideal setting for its growing development. In this paper, bibliometric and scientometric studies are used to analyse the scientific output in the field of research on cultural tourism and its repercussions for rural areas, linking it to depopulation. This is a novel research project in that it analyses all scientific output using the Web of Science (WoS) platform, owned by Clarivate Analytics, as a database. The tool chosen to construct and visualise the data was the VOSviewer software, based on a time frame that spans the last twenty years (2002-2022). Thus, the evolution of all publication and citation records has been assessed and analysed. Likewise, the most important publications and most noteworthy authors, affiliations and countries have been identified. Finally, the study expounds that emerging themes are growing every year at an exponential rate.